1999
DOI: 10.1002/(sici)1097-4628(19991010)74:2<428::aid-app26>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Development of new ionomer blend membranes, their characterization, and their application in the perstractive separation of alkenes from alkene-alkane mixtures. I. Polymer modification, ionomer blend membrane preparation, and characterization

Abstract: ABSTRACT:In this contribution, the synthesis and characterization of novel ion-exchange blend membranes which contain the SO 3 Ag group for the application in the perstractive separation of alkene-alkane mixtures, where the Ag ϩ ion serves as facilitated transport site for the alkene via formation of a pi complex with the alkene double bond, is presented. In this part of the article, the synthesis and characterization of following blend membrane types are described: (1) acid-base blend membranes of ortho-sulfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The transport properties of the two materials are typical for these classes of membrane materials, based on perfluorinated and hydrocarbon polymers. This is clear from a compilation of D σ , D H 2 O , and D H 2 O P data for a variety of membrane materials, including Dow membranes of different equivalent weights, 226,255,260 Nafion/SiO 2 composites 243,244,[304][305][306] (including unpublished data from the laboratory of one of the authors), cross-linked polyarylenes, [307][308][309][310][311][312][313][314][315] and sulfonated poly-(phenoxyphosphazenes) 301 (Figure 19). The data points all center around the curves for Nafion and S-PEK, indicating essentially universal transport behavior for the two classes of membrane materials (only for S-POP are the transport coefficients somewhat lower, suggesting a more reduced percolation in this particular material).…”
Section: Hydrated Acidic Polymersmentioning
confidence: 99%
See 2 more Smart Citations
“…The transport properties of the two materials are typical for these classes of membrane materials, based on perfluorinated and hydrocarbon polymers. This is clear from a compilation of D σ , D H 2 O , and D H 2 O P data for a variety of membrane materials, including Dow membranes of different equivalent weights, 226,255,260 Nafion/SiO 2 composites 243,244,[304][305][306] (including unpublished data from the laboratory of one of the authors), cross-linked polyarylenes, [307][308][309][310][311][312][313][314][315] and sulfonated poly-(phenoxyphosphazenes) 301 (Figure 19). The data points all center around the curves for Nafion and S-PEK, indicating essentially universal transport behavior for the two classes of membrane materials (only for S-POP are the transport coefficients somewhat lower, suggesting a more reduced percolation in this particular material).…”
Section: Hydrated Acidic Polymersmentioning
confidence: 99%
“…318 The gas permeability is much . Transport coefficients of diverse membranes based on perfluorinated polymers (Dow 226,255,260 and Nafion/ silica composites 174,243,244,[304][305][306] ), polyarylenes (S-PEK/PSU blends, ionically cross-linked S-PEK/PBI), [307][308][309][310][311][312][313][314][315] and sulfonated poly(phenoxyphosphazene)s (S-POPs), 301 as a function of the water volume fraction X V . Lines represent data for Nafion and S-PEK (given for comparison); for data points, see Figure 14.…”
Section: Pbi−h 3 Po 4 Adductsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kerress group synthesized several different types of basic, sulfonated or sulfinated polymer, and developed blend concepts for the fuel cell ionomer membranes [107][108][109][110][111][112][113][114][115][116][117][118][119][120][121][122]. Different types of polyaryl blend membranes -that is, ionic, ionic-covalent, and covalent crosslinking -have been studied, and the results have shown that, in the case of ionic crosslinking, the ionic bonds have an unsatisfactory thermal stability which makes the use of such membranes questionable.…”
Section: Reinforced Composite Membranesmentioning
confidence: 99%
“…Polymer electrolyte membrane fuel cell (PEMFC) could offer high power density and efficiency with near-zero emission for various applications such as electric vehicles, potable electronics and residential power generation, etc (1)(2)(3). However, Nafion ® membrane must be well hydrated to obtain an optimum performance because its proton conduction relies on dissociation of protons from ion exchange group in the presence of water (4)(5)(6). PEMFC operating at high temperatures above 80 o C offers various advantages such as higher system efficiency, better water management and negligible catalyst poisoning by carbon monoxide (7-10).…”
Section: Introductionmentioning
confidence: 99%